The Activated Clotting Time Paradox: Relationship Between Activated Clotting Time and Occlusion of the Radial Artery When Used as Vascular Access for Percutaneous Coronary Procedures. (September 2019) - Pacchioni, Andrea; Ferro, Jayme; Pesarini, Gabriele; Mantovani, Riccardo; Mugnolo, Antonio; Bellamoli, Michele; Penzo, Carlo; Marchese, Giuseppe; Benedetto, Daniela; Turri, Riccardo; Fede, Alfredo; Benfari, Giovanni; et al.
Abstract : Background: Radial artery occlusion (RAO) is a thrombotic complication of transradial catheterization that can lead to permanent occlusion of the radial artery. Sheath-vessel diameter ratio, postprocedure compression time, occlusive hemostasis, and insufficient anticoagulation are all predictors of RAO. However, excessive anticoagulation can lead to longer time to achieve complete hemostasis and less patent hemostasis rate. This study was designed to assess the relationship among residual anticoagulation at the end of a percutaneous coronary procedure and the risk of RAO. Methods: Eight hundred thirty-seven patients undergoing transradial catheterization were enrolled. Activated clotting time (ACT) was measured before sheath removal. Patients were divided into 3 groups according to ACT values (ACT <150 s, ACT between 150 and 249 s, ACT >250 s), patent hemostasis with reverse Barbeau test was attempted in all patients, and compression device removed as soon as possible. Within 24 hours, patency of radial artery was checked by Doppler using reverse Barbeau technique. Results: Incidence of RAO was higher for the extreme ACT values. Patent hemostasis were less frequently obtained and time to hemostasis significantly longer for increasing ACT values ( P =0.004 for trend and <0.0001 for trend, respectively). At logistic regression analysis, ACT values <150 s were an independent predictor of RAO (odds ratio, 3.53; 95% IC, 1.677–7.43; P =0.001) while adjusted probability for RAO confirmed U-shaped relationship with ACT values. Conclusions: The level of anticoagulation is strongly related to incidence of RAO and should be measured objectively by ACT. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02762344. Abstract : Supplemental Digital Content is available in the text.